2013
DOI: 10.1021/cb400140u
|View full text |Cite
|
Sign up to set email alerts
|

Donor Assists Acceptor Binding and Catalysis of Human α1,6-Fucosyltransferase

Abstract: α1,6-Core-fucosyltransferase (FUT8) is a vital enzyme in mammalian physiological and pathophysiological processes such as tumorigenesis and progress of, among others, non-small cell lung cancer and colon carcinoma. It was also shown that therapeutic antibodies have a dramatically higher efficacy if the α1,6-fucosyl residue is absent. However, specific and potent inhibitors for FUT8 and related enzymes are lacking. Hence, it is crucial to elucidate the structural basis of acceptor binding and the catalytic mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 44 publications
3
15
0
Order By: Relevance
“…This dimer could be observed in the previously determined apo structure of FUT8 21 , yet the structure was reported on as a monomer. Other publications have reported that HsFUT8 is a monomer in solution, based on size exclusion chromatography experiments 33 , and this has influenced the way in which molecular dynamics and docking simulations of FUT8 have been conducted 22,23 , potentially compromising their conclusions. To address this inconsistency in the literature, we performed SEC-SAXS on FUT8 ( Figure 4B,C), which conclusively demonstrated that FUT8 exists as a dimer in solution.…”
Section: Fut8 Dimerisation and Orientation Of Sh3domain For Acceptor mentioning
confidence: 99%
See 1 more Smart Citation
“…This dimer could be observed in the previously determined apo structure of FUT8 21 , yet the structure was reported on as a monomer. Other publications have reported that HsFUT8 is a monomer in solution, based on size exclusion chromatography experiments 33 , and this has influenced the way in which molecular dynamics and docking simulations of FUT8 have been conducted 22,23 , potentially compromising their conclusions. To address this inconsistency in the literature, we performed SEC-SAXS on FUT8 ( Figure 4B,C), which conclusively demonstrated that FUT8 exists as a dimer in solution.…”
Section: Fut8 Dimerisation and Orientation Of Sh3domain For Acceptor mentioning
confidence: 99%
“…To some degree, drug discovery efforts are impeded by a limited structural understanding of this enzyme and the mechanism it employs to perform core fucosylation. The only reported FUT8 structure possesses no bound ligands, 21 and our only insights into donor and acceptor substrate binding come from STD-NMR, molecular dynamics and docking studies 22,23 . To gain a thorough understanding of how FUT8 recognises both its donor and acceptor substrates to catalyse core fucosylation, we revisited the structural biology of FUT8.…”
Section: Introductionmentioning
confidence: 99%
“…This dimer could be observed in the previously determined apo structure of FUT8 21 , yet the structure was reported on as a monomer. Other publications have reported that HsFUT8 is a monomer in solution, based on size exclusion chromatography experiments 33 , and this has influenced the way in which molecular dynamic and docking simulations of FUT8 have been conducted 22, 23 , potentially compromising their conclusions. To address this inconsistency in the literature, we performed SEC-SAXS on FUT8 ( Figure 4B,C ), which conclusively demonstrated that FUT8 exists as a dimer in solution.…”
Section: Resultsmentioning
confidence: 99%
“…It plays an important role in the tumorigenesis of non-small cell lung cancer and colon carcinoma [96,97] . Human Fut8 gene is located on chromosome 14q23.3, and consists of at least nine exons spanning more than a 50 kb genomic region, and the coding sequence is divided into eight exons [98,99] .…”
Section: T-synthasementioning
confidence: 99%